Shaping Foundational Learning Skills: A Harbinger to the Future of Work - Chandra , Reetu (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
The acquisition of fundamental skills in early childhood is foundational for future learning and holistic development, aligning with the Sustainable Development Goals' objective of promoting early literacy and numeracy. However, the State of Global Learning Poverty report indicates a concerning trend, with global learning poverty reaching 70% in low- and middle-income countries, highlighting the challenge of children struggling with basic literacy by age 10. India has taken proactive measures through the National Education Policy 2020 and the launch of the 'National Initiative for Proficiency in Reading with Understanding and Numeracy' (NIPUN Bharat) in 2021 to ensure universal access to essential reading and numeracy skills by Grade III. This study employs a mixed-methods research approach, incorporating both qualitative and quantitative methodologies to assess the effectiveness of India's initiatives in promoting foundational learning. Qualitative analysis involves examining policy documents, curriculum materials to understand the implementation process and challenges faced. Quantitative assessments include analysing educational data from the academic year 2021–22, particularly focusing on enrollment rates, learning outcomes, and the impact of interventions on children aged three to eight. These results show that India has taken a lot of steps to improve basic education. In this work, I identify challenges such as disparities in preschool attendance and pedagogical approaches that prioritise rote learning, which require comprehensive solutions involving teacher training, curriculum development, and parental engagement. Thus, as India assumes leadership within the G20, there is an unprecedented opportunity for global collaboration to advance foundational learning agendas. By sharing best practices, mobilising resources, and fostering multilateral partnerships, nations can collectively accelerate progress towards achieving Sustainable Development Goal 4, ensuring inclusive, equitable, and quality education for all. Ultimately, the attainment of foundational learning skills for children is not only an educational necessity but a moral imperative. Through sustained commitment, collaborative action, and unwavering resolve, we can unlock the full potential of future generations and pave the way for a brighter, more prosperous future worldwide.